AN ANALYSIS OF TRANSLATION PROCEDURES BASED ON PINCHUCK'S FRAMEWORK IN THE INDONESIAN TRANSLATION OF ACEHNESE HADIH MAJA ON THE OFFICIAL WEBSITE OF JULI DISTRICT, BIREUEN - Isti Komah; Zainuddin Hasibuan; Fathin Hidayati; Raihan Musfirah; Putri Nurul Aulia (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2026)
Hadih maja is an Acehnese cultural heritage containing advices, proverbs, and philosophical expressions that reflect moral, social, and cultural values. As times progress, the use of local languages decreases, necessitating efforts to introduce hadih maja to a wider audience through translation. Although there have been a number of studies on the translation of cultural expressions and proverbs, research that specifically analyzes the translation procedures of Acehnese hadih maja based on Pinchuck’s (1977) framework, particularly those sourced from official digital media, remains limited. This limitation indicates a research gap in the study of Acehnese cultural text translation. This research aims to describe the translation procedures used in translating Acehnese hadih maja from the source language into Indonesian as the target language, while integrating it as a contributive effort to preserve local language materials in education. The method used was descriptive qualitative through literature review techniques. From a population of 96 hadih maja data, 15 sample data were selected from an article by Teuku Muhammad Hanis, S.E., published on September 16, 2023, on the official website of Juli District, Bireuen Regency, to be analyzed deeply based on translation procedure theory. The results show that out of 15 analyzed data, the translation procedures were dominated by two types: literal translation with 8 data (53.33%) and modulation with 7 data (46.67%). Other procedures such as translation, transliteration, borrowing, transposition, and adaptation were not found. These findings indicate that the translation of hadih maja does not rely solely on linguistic equivalence, but also on the translator’s ability to perform a shift in perspective (modulation) in order to preserve the cultural meaning and moral messages embedded within the expressions. Thus, the translation process plays an important role as a form of cultural mediation in the transfer of meaning across languages. Theoretically, this study enriches translation studies by demonstrating how Pinchuck’s procedures operate in texts based on local wisdom. Practically, the results of this study can serve as a reference for translators, educators, and researchers in understanding strategies for translating culturally bound texts with rich contextual meanings.